2019
DOI: 10.1177/0706743718818417
|View full text |Cite
|
Sign up to set email alerts
|

The Decline of Child Sexual Abuse in Canada: Evidence From the 2014 General Social Survey

Abstract: Objective: To provide evidence of trends in child sexual abuse (CSA) in Canada. Methods: Using data from 15,801 males and 18,669 females who responded to the 2014 General Social Survey (GSS), we compared the prevalence of CSA by age cohorts. Age cohort patterns were examined for several sub-populations including males, females, Indigenous peoples, and people living in low-income households. Results: After an increase in the post-World War II period, there has been a decline in CSA in Canada since the early 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…5,25,26 Similarly, results from the Canadian component of the GENACIS project (Gender, alcohol and culture: an international study) showed that child sexual abuse rates declined after 1993 but were significantly higher between 1946 and 1992 compared with the period before 1946. 26,27 The reasons for higher reporting of ACEs among the 1950-1969 birth cohort in our study is unclear, but examining the trauma and disruptions after World War II may help to explain these time trends. 26 It is also possible that the reporting of ACEs may be affected by secular trends.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…5,25,26 Similarly, results from the Canadian component of the GENACIS project (Gender, alcohol and culture: an international study) showed that child sexual abuse rates declined after 1993 but were significantly higher between 1946 and 1992 compared with the period before 1946. 26,27 The reasons for higher reporting of ACEs among the 1950-1969 birth cohort in our study is unclear, but examining the trauma and disruptions after World War II may help to explain these time trends. 26 It is also possible that the reporting of ACEs may be affected by secular trends.…”
Section: Discussionmentioning
confidence: 77%
“…26 Younger individuals may be more likely to acknowledge and report maltreatment as an effect of increased media coverage, whereas lower reporting among older individuals may be because of their reluctance to disclose experiences, which may be viewed as stigmatizing during the period in which they were born. [25][26][27][28] In addition, prevalence in the oldest age group may be influenced by premature mortality experienced by individuals exposed to ACEs. 29 Our findings showed that exposure to ACEs varied across Canadian provinces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-pandemic nationally representative trend data on household violence in Canada are limited. Studies using national survey data have found evidence of a decline in childhood sexual abuse since 1990 [ 17 , 18 ] and a decrease in childhood physical abuse among those born between 1980 and 1999 (birth cohort) [ 19 ]. Statistics Canada, Canada’s national statistics agency, has also found a decline in self-reported spousal violence since 2004 [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dependency on this kind of data relies on the assumption that all instances of sexual abuse is reported. Aside from the alarming reality that these statistics are not accessible to estimate how prevalent an issue CSA in Canada is, the existing national data is less than optimal (Shields et al, 2019). What the limited and most recent literature suggests is that child sexual abuse prevalence has decreased between the years 1945 earlier to present.…”
Section: Child Sexual Abuse and Disclosurementioning
confidence: 99%